Upaya Guru dalam Adaptasi Manajemen Kelas untuk Efektivitas Pembelajaran Daring - Nanik Margaret Tarihoran; Wiputra Cendana (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2020)
In carrying out the role, a teacher has difficulty managing the class so that learning does not run effectively. Class management is the problem faced by the teacher in the first teaching during field experience at a Christian school in Lampung. The purpose of this paper is to describe the teacher's efforts to adapt classroom management in achieving effective online learning. This paper had written through descriptive qualitative methods. Based on the study conducted, the adaptation of online classroom management had carried out by improving learning plans, improving teaching methods through lectures and discussions, and providing supporting material by Word, besides PowerPoint with sound and video. This paper concludes that the adaptation of classroom management helps teachers in carrying out online learning effectively. The suggestions given by the writer are (1) Adjusting strategies, methods, models, and time allocation with the teaching materials in the lesson plans, (2) Providing supporting material to easily accessible by students; (3) Providing feedback to students who are learning asynchronously via Facebook, Email, Google Classroom, and so on; (4) Visiting students if schools and students are unable to carry out online learning with permission from various parties (foundations, schools, parents, and the government).